Upper Canadian Thermidor: The Family Compact & the Counter-revolutionary Atlantic - McKim, Denis (Ontario History, 2014)
This article challenges the notion that the Family Compact was a self-interested clique who stunted Upper Canada’s political, social, and economic development. It argues, instead, that members of the group articulated a dynamic vision for the colony premised on the “balanced” British constitution, state-aided Anglicanism, and a vibrant agrarian economy led by a paternalistic elite. Of central importance to the Compact’s vision for Upper Canada was a longstanding conservative tradition that had its roots in late-seventeenth-century England, and was reinforced a century later by a multifaceted counter-revolutionary phenomenon that manifested on both sides of the Atlantic Ocean.